The comparison of islamic and conventional banking in ownership structure and interest rates in Indonesia - Hartini, Titin; Lidyah, Rika; Safitri, Nurfala (Universitas Bangka Belitung, 2024)
Ownership structure and interest rates are important factors affecting a bank's performance. Previous studies have found the effect of ownership structure and interest rates on company performance, but no one has specifically examined differences in Banking performance in ownership structure and interest rates. This study aims to compare the performance of Islamic and conventional banking in ownership structure and interest rates. In study, the author used quantitative methods that emphasize the analysis of numerical data processed using Stata 16. Based on the unstructured data panel, there are 13 Islamic banking and 107 conventional banking, the total banks used as objects are 120 banks with 1110 observations. The results are local ownership did not affect the performance of Islamic banks, compared to conventional banking on the contrary. Foreign ownership in Islamic banking affects Banking performance, while conventional banking has no effect. Furthermore, government ownership affects the performance of Islamic banks, but does not affect the performance of conventional banking. Based on the results of the study, it can be proven that government and foreign interference in the ownership of Islamic banking plays a role in improving the bank's performance. Whereas conventional banking has performed well under local ownership.